Bagaimana Kualitas Produk, Harga dan Promosi Meningkatkan Kepuasan Pelanggan pada Industri Rokok Golden Taste 88 - Qomariah, Nurul; Pardede, Adinda Jennifer; Kamil, Ibrahim; Asalia, Nadia; Nurbayani, Siti (BUDGETING : Journal of Business, Management and Accounting, 2024)
ABSTRACT The cigarette industry is one industry that can contribute to PAD. Increasing competition in all lines of business means that the cigarette industry must also be able to determine marketing strategies in order to survive in business. The aim of this research is to determine the impact of product quality, price and promotion on customer satisfaction among consumers who consume Golden Taste 88 cigarettes. The population in this research is consumers who use Golden Taste 88 cigarettes in Bondowoso, East Java. The number of samples was determined at 100 respondents. To answer the proposed hypothesis, multiple linear regression analysis was used. After carrying out analysis using various analytical tools, the results of this research are: the quality of Taste 88 Cigarette products has succeeded in providing increased customer satisfaction. The prices set by Taste 88 Cigarettes can increase customer satisfaction. Promotions carried out by Taste 88 cigarettes can provide customer satisfaction. Keywords: Customer Satisfaction, Product Quality; Price; Promotion.